Variability in fecal egg count of Haemonchus contortus infection to native goat breeds of China and Bangladesh under natural grazing condition - Omar, AI; Alam, MBB; Faruque, MO; Mondal, MM; Raihan, MS; Adetula, AA; Wu, Z; Bhuiyan, AA; Soudy, F; Cao, J; et al. (Progressive Agriculture, 2017)
Haemonchus contortus is a major gastrointestinal nematode affecting goat in China and Bangladesh like many countries in the world. The aim of this study was to evaluate the susceptibility of Haemonchus contortus infection in different goat breeds/populations in China and Bangladesh under the natural grazing condition. Fecal Egg of Haemonchus contortus was counted from 430 goats in both countries using McMasters technique. Body weight, Pack Cell Volume and Hemoglobin value were measured for Bangladeshi goats. Statistical analysis was done after transforming data into log10 (n+1), where n is the number of egg per gram feces and analysis of variance was done by using Generalized Linear Model procedures of computer package of SAS. Prevalence of parasite and Fecal Egg Count varied significantly (P<0.01) in all six goat populations. The highest prevalence (88.89%) of Haemonchus contortus infection was found in Enshi Black and the highest parasitic load (527.74 ±78.13 epg) was found in Chinese hybrid goat population. Most of the individuals, except Chinese hybrid goats, had Fecal Egg Count less than 300 epg. Fecal Egg Count between sexes within breed of goat did not differ significantly (P>0.05). Black Bengal goat in the hilly region of Bangladesh was the least susceptible to Haemonchus contortus infection in term of Fecal Egg Count. Our study suggests that Chinese goat breeds were more susceptible to Haemonchus contortus infection as compared to Black Bengal goat of Bangladesh under natural grazing condition. Further studies on immune-genetics aspects of goats might be helpful to find out the actual causes of such differences and to develop disease resistant breed of goat. Progressive Agriculture 27 (4): 473-481, 2016